2016
DOI: 10.1016/j.jpsychires.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation as an adjunct therapy for obsessive-compulsive disorder: A randomized controlled study

Abstract: Background: Transcutaneous electrical acupoint stimulation (TEAS) is thought to have potential to treat obsessive-compulsive disorder (OCD).Objective: The purpose of this study was to determine whether adding TEAS to cognitive behavioral therapy (CBT) and clomipramine would improve the efficacy of these conventional treatments in OCD.Methods: In this randomized controlled trial, 360 OCD patients were assigned to receive TEAS combined with CBT plus clomipramine (Group A, n = 120), TEAS combined with CBT plus pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…This indicates that additional TEAS augments the efficacy of antidepressants or CBT in improving PTSD. This is consistent with our previous studies, showing that additional TEAS enhanced the effectiveness of antidepressants and CBT in patients with OCD and earthquake‐related PTSD . The present participants represent a PTSD subpopulation with diverse etiological profile because they had experienced various traumatic events.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that additional TEAS augments the efficacy of antidepressants or CBT in improving PTSD. This is consistent with our previous studies, showing that additional TEAS enhanced the effectiveness of antidepressants and CBT in patients with OCD and earthquake‐related PTSD . The present participants represent a PTSD subpopulation with diverse etiological profile because they had experienced various traumatic events.…”
Section: Discussionsupporting
confidence: 92%
“…Simulated TEAS was conducted as previously reported . Briefly, adhesive electrode pads were placed at sites 1 cm radial to Nei‐Guan (PC6) and the stimulation intensity was adjusted to the minimum sensory threshold for 30 s and then ramped off over the next 15 s so that it was active for a total of 45 s. This transient stimulation has been well validated and found to better maintain blinding compared with standard placebo‐TENS methods, in which no current was actually delivered to the electrodes …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In der Behandlung von Traumafolgestörungen wurde die Wirkung von Akupunktur in Akupunktur in der Psychiatrie Praxis zkm te auch hier in einer Studie eine Wirkverstärkung konventioneller Therapiemethoden bei Abnahme von Nebenwirkungen durch Akupunktur gefunden werden [104].…”
Section: Traumafolgestörungenunclassified
“…We previously performed a randomized controlled trial of transcutaneous electrical acupoint stimulation (TEAS) that showed good efficacy for OCD; in the present study, we improved this treatment to obtain a more rapid effect. 6…”
Section: Introductionmentioning
confidence: 99%